Information technology. Telecommunications and information exchange between systems. Transport conformance testing for connection-mode transport protocol operating over connection-mode network service. Abstract test suites and PIXIT for ISO/IEC 8073:1988 classes 0, 2 over CONS and 4 over CLNS Part 2, (15th May 1997) - British Standards Institution,
No abstract available